Atypical McCune--Albright syndrome associated with GH secreting pituitary adenoma - Pemovska, Gordana; Volkanovska-Ilijevska Cvetanka; Krstevska, Brankica; Ahmeti, Irfan (Bioscientifica, 2013)
McCune–Albright syndrome (MAS) is characterized by fibrous dysplasia (FD), cutaneous cafe-au-lait pigmentation and autonomous hyper-secretory endocrinopathies. Association of acromegaly with MAS is very rare. We present a case of a 35-year-old men with MAS, diagnosed with poly-ostotic fibrous dysplasia at the age of 12, no history of premature puberty, with GH secreting cystic macroadenoma 40×35×45 mm big and clinical picture of acromegaly, hypopituitarism and bilateral hemianopsia. FD was diagnosed based on the clinical picture, radiological findings and bone scan. Base values of the hormones were: GH 16.6 ng/ml with absent supression OGGT, IGF1 >1100 ng/ml, IGFBP=9800 mg/ml, PRL >470 mg/ml. Our patient was treated with somatostatin analog, Octreotide 3×0.1 mg for 2 months prior to transfenoidal surgery. Due to residual and activity of acromegaly, the patient was treated with external irradiation and dopamine agonist Bromergon until normal values of GH/IGF1 were achieved. One year after the surgery, FD of cranofacial bones caused fascial assymetry, ptosis of the right eyelid, strabismud, sight imparements. After Craniotomia frontotemporalis dex. Decompresion.optici dex. were performed, the symptoms disappeared. The pathohistological findings showed Osteoma (FD) of the scalp in the right occipital region. The patient is on substitution therapy with L-thyroxine, testosterone and bisphophonate. As conclusion, primary treatment of large pituitary mass is surgery. Nonsurgical treatment, in inoperable patients due to bony involvement of the skull are somatostatin analogs, radiotherapy and dopamine agonists at maximal doses.
Keywords: McCune–Albright syndrome, acromegaly.